Queerizando o cânone: uma leitura assexual de Jo March em Little Women, de Louisa May Alcott - Costa, Priscilla Thuany Cruz Fernandes da (2024)
American writer Louisa May Alcott's novel Little Women, published in 1868, has been the subject of intense academic interest in the field of Feminist and Gender Studies and remains culturally relevant today. One theme stands out among the discussions about literature and its intersection with issues of gender and sexuality with regard to the novel in focus: the possible queer [re]readings of the protagonist Jo March developed in the academic and literary fields. Stemming from a queer perspective, this work focuses on asexuality and how its representation in literature has been gaining dimension both in contemporary texts and in revisited classics. Thus, the proposal of this research consists of developing a reading of the novel Little Women, through the use of a theoretical-critical framework produced in what is currently understood as the field of asexuality studies. Firstly, I gather biographical elements about Louisa May Alcott as well as information about the content, historical context, and reception of her novel. Next, I present a brief historical contextualization of asexuality and some of the main concepts that support the theoretical field of asexuality studies. To this end, the research brings as its main references the contributions of Ela Przybylo, Elisabete Regina Baptista de Oliveira, KJ Cerankowski and Megan Milks to contemporary studies on asexuality. In the final chapter, I seek to produce an asexual reading of Little Women focusing on the character Jo March, bringing together excerpts from the novel in light of the categories of analysis presented, highlighting the character's resistance to compulsory sexuality, amatonormativity and current sexonormative scripts.